Synthesis and Characterization of Functionalized Benzimidazole Derivatives: A Practical Experimental Study (Scientific Journal for Publishing in Health Research and Technology, 2025)
A series of functionalized benzimidazole derivatives were successfully synthesized and characterized to enhance their biological activity, achieving yields ranging from 70% to 85% using standard condensation and functionalization processes. The structures of the compounds were verified through mass spectrometry (MS), infrared spectroscopy (IR), and nuclear magnetic resonance (NMR) spectroscopy, which provided comprehensive structural insights. Evaluation of antimicrobial activity against S. aureus and E. coli demonstrated that derivatives 1c and 1d exhibited notable inhibitory zones. Furthermore, cytotoxicity tests using HeLa and MCF-7 cell lines showed potent anticancer activity, with compounds 1c and 1d displaying lower IC50 values compared to those reported in earlier research. These results suggest that specific structural alterations can markedly increase the biological efficacy of benzimidazole derivatives, indicating their strong potential as antimicrobial and antitumor drugs. Future research should focus on investigating a larger spectrum of biological functions, employing new synthesis techniques, and carrying out comprehensive mechanistic and pharmacokinetic studies to fully realize the therapeutic promise of these molecules.
Keywords: Benzimidazole derivatives; synthesis; functionalization; antimicrobial activity; cytotoxicity; NMR spectroscopy; IR spectroscopy; mass spectrometry; ructure-activity relationship; medicinal chemistry